Keynesianism as foundation of the key economic policies in the context of the Global Economic Crisis - the case of R. Macedonia - Trenovski, Borce (Faculty of Economics – Skopje, University Ss. Cyril and Methodius, Skopje, 2017)
The paper first elaborates Keynesian concept, its main characteristics and the recommendations Keynesianism provides for macroeconomic policies implemented during economic disturbances and crises. Furthermore, it focuses on the response of the key macroeconomic policies (fiscal and monetary) in terms of the Global Economic Crisis and the period of recovery in the Republic of Macedonia. Finally, the paper analyzes the elements of key economic policies in response to the global economic crisis in the context of main Keynesian assumptions/postulates (in Macedonia). The analysis finds out that the Keynesian economic theory was predominantly the basis of the economic policies undertaken in the time of global crisis (also the period of recovery) in Macedonia. Furthermore, it should be taken into consideration that it is extremely difficult to isolate only one economic concept as the sole basis of economic policies in terms of economic disturbances, and that in Macedonia, in some part, there is a mixture of economic concepts as determinants of economic policies efficiency in the time of the global economic crisis.
Keywords: Keynesianism, economic theory, economic cycles, monetary policy, fiscal policy, Macedonia, global economic crisis.